Integrated Approach of Yoga and Naturopathy for Longevity -A review - Sethi, Meena Kumari; Yogi, Rajendra P (International Research Journal of Ayurveda & Yoga, 2022)
Yoga & Naturopathy plays an important role in maintaining proper health and in preventing the ageing process. Several systems of Yoga & Naturopathy have been developed over the years. The most popular & ancient among them are yogic & Naturopathy therapies. Yoga is a means of attaining perfect health by maintaining harmony and achieving optimum functioning on all three levels physical, mental and spiritual through complete self-control. It improves circulation and energies and stimulates major endocrine glands of the body. Yogic exercises promote health and harmony and their regular practice helps prevent and cure many common ailments. Natural healing started giving a new life to the people of new age. Combined with the goodness of nature and exclusive healing principles, Yoga & meditation the health ailments leading to optimal health and wetness in a long run. Naturopathic treatment is a combination of natural remedies, herbs, meditation, yoga and modifications in the life style.